Frontiers of chemical engineering, metallurgical engineering and materials III : selected, peer reviewed papers from the 2014 3 rd International Conference on Chemical Engineering, Metallurgical Engineering and Metallic Materials (CMMM 2014), June 20-21, 2014, Guilin, China - Kao, Jimmy (C. M.); Sung, Wen-Pei; Chen, Ran (Advanced materials research ;, 2014)
Collection of selected, peer reviewed papers from the 2014 the Third International Conference on Chemical Engineering, Metallurgical Engineering and Metallic Materials (CMMM 2014), Guilin, China, June 20-21, 2014. The 192 papers are grouped as follows: Chapter 1: Biotechnology, Medical and Chemical Engineering, Chapter 2: Material Engineering and Technologies, Applied Materials, Chapter 3: Metallurgical and Mining Engineering, Manufacturing Engineering Applications, Chapter 4: Energy and Power, Wells, Resources and Flow Development, Environmental Engineering and Technologies Keyword: Chemical Engineering; Metallurgical Engineering; Metallic Materials; Materials Engineering; Environmental Engineering One hundred ninety-nine papers from the June 2014 conference report research findings on chemical engineering, materials, metals, manufacturing, power generation, and environmental engineering. Three papers from Inner Mongolia University synthesize a zigzag chain cadmium coordination polymer, isostructural transition metal complexes, and SiC/Cu composites. Other topics include black liquor treating of wheat straw pulp using microwave radiation, a dispersant for lithium ion battery slurry, crimping of large diameter welding pipe, manganese removal from electrolytic manganese residue using ozone, and recycling of non-metal waste from printed circuit boards. -- Chemical engineering-- Environmental engineering-- Materials science-- Metals.